An assessment of the renal biopsy technique in the university medical unit, Colombo - De Mel, W.C.P.; Jayasinghe, K.S.A.; Sheriff, M.H.R.; Dharmadasa, K. (My University, 1983)
Renal Biopsies done in Sophisticated Centres in U. K. and U. S. A. involve of I. V. P., ultrasound or CT-Scan control for accurate localisation of the kidney to obtain near 100% results. In view of non availability of the latter two techniques and delay in obtaining routine I. V. P. we have performed Renal Biopsies using minimum facilities available to us. a) X' ray G.U.T. - after good preparation b) Bleeding Time,Clotting Time and Platelet count. c) Approximate measurements from X'ray G. U. T. d) Reusing disposable Trucut needles. 160 Renal Biopsies done from 1979 Jan. to 1982 Dec. using the percutaneous approach on either right or left loin were studied. The indications were Nephrotic Syndrome in adults (128 patients) Recurrent or prolonged course in Acute Nepritic Syndrome (20 patients) Renal Failure - Acute and Rapidly progressive (12 patients). Renal tissue was obtained in 109 patients (70/%). 2 patients had perirenal haematoma requiring 10-12 days hospital stay for the swelling and pain to settle. None of our patients required blood tranfusion or exploration of the loin. There was no instance of infected biopsy sites. The lower rate of successful biopsies was due to several factors. The chief of which was the blunting of Trucut needles after repeated use. The Average number of reuses of our needles was between 7-10 times. With the limited facilities available we have found Renal Biopsy technique using the Trucut needle a reasonably safe procedure to undertake in the evaluation of renal diseases.